Neurology and neurosurgery illustrated - Lindsay, Kenneth W.; Bone, Ian, FRCP; Fuller, Geraint; Callander, Robin (Churchill Livingstone/Elsevier, 2010)
An illustrated guide to neurology and neurosurgery that is suitable for medical students and junior doctors.